Universality Results for Well-Founded Posets - Džamonja, Mirna; Thompson, Katherine (Sarajevo Journal of Mathematics, 2024)
In this paper it is shown that the univerality spectrum of well-founded posets is exactly the same as the spectrum of the class of well-orders. A universality result for a restricted class of well-founded posets under rank and order preserving embeddings is also proved. This is done using a club guessing method generalised by Kojman which demonstrates a surjective homomorphism with subsets of the reals of bounded size ordered by inclusion. 1991 Mathematics Subject Classification. 03E04, 06A05, 06A06